Pengaruh Kualitas Sistem Informasi Akuntansi Terhadap Kepuasan Pengguna Paket Program Aplikasi Sistem Informasi Akuntansi (Studi Empiris pada Bank Perkreditan Rakyat di Kota Boyolali) - Nugraheni S, Isti, Dr. Noer Sasongko, SE, M.Si, Ak (2016)
This study aimed to examine the effect of the quality of information system accounting to satisfaction users package application program accounting. The variables used in this research is the services quality, system quality, information quality, and enduser accounting software satisfaction. The population was all the employess public credit bank in Boyolali. Samples were determined using purposive sampling method. The study had 50 samples of 6 employess public credit bank in Boyolali. Technique analysis the data used was linear regression mutiple. The results of this study show that quality of services affect the user satisfaction with the level of significance 0.046 < 0.05. The first hypothesis is accepted. quality of system affect the user satisfaction with the level of significance 0.026 < 0.05.Maka second hypothesis is accepted. quality of information affect the user satisfaction with the level of significance 0.041 < 0.05. The third hypothesis is accepted.